Reduction of phosphorus concentration in mineral supplement on fertility rate, maternal ability and costs of beef cows reared in pastures of Urochloa decumbens - Costa, Rogério Magnoli; Ponsano, Elisa Helena Giglio [UNESP]; de Souza, Vinícius Carneiro [UNESP]; Malafaia, Pedro (Springer Nature, 2016)
Manufacturing and marketing of mineral mixtures with less than 40 g kg−1 phosphorus (P) is prohibited under Brazilian regulations, although scientific evidence rejects this recommendation. Considering the hypothesis that P levels in commercial mineral supplements can be reduced without affecting animal performance and health, the objective of this experiment was to evaluate the effects of reducing the concentration of P in the mineral supplement (from 40 to 18 g kg−1) of a herd of beef cows grazing tropical pastures of signal grass (Urochloa decumbens). The experiment was carried out in the savanna region of Mato Grosso do Sul, Brazil, during the years 2011 to 2013. Variables analyzed included pregnancy rate, calving interval, weight of calves at weaning, and cost of mineral supplementation. There were no changes in the reproductive parameters of the herd and the weight at weaning of the calves. However, the cost of mineral supplementation was significantly lower when the herd was supplemented with the mineral mix containing only 18 g kg−1 P. Phosphorus concentration of the forage was analyzed monthly during 1 year and averaged 1.9 ± 0.45 g kg−1 DM. Thus, it appears possible to reduce P content and cost of mineral supplementation without any adverse effects on the health and productivity of beef cattle herds in the State of Mato Grosso do Sul. However, the final decision should be made based on the clinical-nutritional examination and by constant technical assistance to the farm.
Keywords: Beef cattle; Cost of mineral supplementation; Phosphorus